48.7k views
3 votes
the sum of three numbers is 62 the second number is equal to the first number diminished by for the third number is four times the first ​

User Maxymus
by
5.8k points

1 Answer

5 votes

Answer:

11, 7, 44

Explanation:

a+b+c = 62

a-4 = b

c = 4×a

I think you meant "diminished by four", right ?

=>

a + a-4 + 4×a = 62

6×a - 4 = 62

6×a = 66

a = 11

=>

b = 11 - 4 = 7

c = 4×11 = 44

User Leprechaun
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.